Characteristics of Edible Bowls Made from Papaya Skin as an Effort to Tackle Plastic Waste in Indonesia - Wulandari, Tiara Dwi; Kinasih, Cahyani Putri; Syahbananto, Gilang; Listiaji, Prasetyo; Ramadhani, Nisfil Amelia (Universitas Negeri Semarang, 2023)
Synthetic plastic made from the synthetic polymer polypropylene (PP) is generally used as food packaging, which over time causes environmental problems, so innovation in food packaging in the form of edible bowls is needed. Edible bowls are made from papaya skin pectin, wheat flour, gelatin flour, vegetable oil and water which are baked using oven technology. Based on tests, edible bowls have a water absorption capacity of 3% to 23%, can last for 18 minutes at a high temperature of 90℃ and 31 minutes at a temperature of -10℃, and can decompose within 2 to 3 months. This edible bowl made from papaya skin is an alternative substitute for plastic packaging, thus tackling the problem of plastic waste in Indonesia.